The effect of katuk leaf (Sauropus androgynous L. merr) extract administration on reducing blood triglyceride levels in male local rabbits induced with hypercholesterolemia - Khalid, Idham; Ferasyi, Teuku Reza; Sugito, Sugito; Hafizsha, Nabila Latifa; Ulfa, Rasyida; Fitriana, Rizky; Makmur, Ali (The International Journal of Tropical Veterinary and Biomedical Research, 2024)
This research aimed to study the effectiveness of katuk leaf extract in lowering blood triglyceride levels in male local rabbits treated with hypercholesterolemia. The research was done at the Laboratory of Veterinary Public Health and the Animal Experimental Unit of the Faculty of Veterinary Medicine, Universitas Syiah Kual. This experiment used the Split Plot design, comprising two factors. The first factor was treatment (P1, P2, and P3) that gives katuk leaf extract 2.5 cc, 5 cc, and 10 cc, whereas the second factor was the sampling time (I, II, III, IV, and V). The results of this research showed that the treatment did not significantly (P0.05) on levels of triglycerides in the blood of local rabbits. Still, different sampling times were very significant (P 0.01) on levels of triglycerides in the blood of local rabbits. After doing Duncan tests, the results test showed that the sampling time between a decrease of local rabbit blood triglyceride levels was not significant (P0.05) by giving katuk leaf extract. The treatment of katuk leaf extracts of 2.5 cc, 5cc, and 10cc has not been able to reduce levels of triglycerides in the blood of male local rabbits treated with hypercholesterolemia.